The Role of Artificial Intelligence in Business and Management Decision-making: A Bibliometric Analysis to Map the Scientific Discourse - Munnisunker, Shivaan; Szalay, Zsigmond Gábor (Acta Carolus Robertus, 2025)
The role of artificial intelligence (AI) in business and management decision-making has become one of the most intensively studied areas in recent years. The present study conducts a bibliometric analysis based on 4,165 publications in the Web of Science database in order to map the main structural and thematic characteristics of the scientific discourse. It is possible to identify three dominant scientific clusters based on the co-occurrence of keywords, co-citation networks, and scientific collaborations between countries. The following three approaches have been identified: firstly, technology- and algorithm-focused approaches; secondly, organisational and human-centred interpretations; and thirdly, research based on business decision support and information management. The objective of the present study is to emphasise that AI is not merely a technological innovation, but rather an interdisciplinary phenomenon that fundamentally transforms the organisational, ethical and strategic frameworks of decision-making. The results obtained contribute to a more accurate understanding of research trends in the field and provide a basis for further analysis.